Synthesis, characterization and anticancer activity of palladium allyl complexes bearing benzimidazole-based N-heterocyclic carbene (NHC) ligands. (1st October 2021) - Scattolin, Thomas; Piccin, Andrea; Mauceri, Matteo; Rizzolio, Flavio; Demitri, Nicola; Canzonieri, Vincenzo; Visentin, Fabiano
Graphical abstract: The synthesis of twelve new palladium allyl complexes bearing benzimidazole-based NHC (NHC = N -heterocyclic carbene) ligands is reported. Comparing the IC50 values of mixed NHC/PTA complexes reported in this work and their trifluoromethyl congeners recently published by our group, it appears evident that they have very similar antiproliferative activity against cancer cells but the absence of the CF3 significantly decreases the selectivity toward them. Abstract: The synthesis of twelve new palladium allyl complexes bearing benzimidazole-based NHC (NHC =  N -heterocyclic carbene) ligands is reported. All the complexes were characterized by NMR and elemental analysis and, in the case of complex 5c, it was possible to confirm the connectivity by single crystal X-ray diffraction. The cationic palladium allyl complexes were tested toward 5 different cancer lines, with IC50 values generally lower than cisplatin and similar antiproliferative activity in the two ovarian cancer cell lines (A2780 and A2780 cis ), suggesting a different mechanism of action from classical platinum-based anticancer drugs. Compounds equipped with a pyridine arm or with the NHC/PTA combination (PTA = 1, 3, 5-triaza-7-phosphaadamantane) showed a lower cytotoxicity on normal cells with respect to cancer ones. By comparing the IC50 values of mixed NHC/PTA complexes reported in this work and their trifluoromethyl congeners recently published by our group, it appears evident that they have very similar antiproliferative activity against cancer cells but the absence of the CF3 group significantly decreases the selectivity toward them.